The effects of glass as partial replacement of fine aggregate in concrete / Yaaser Hasbullah and Nurul Asra Abd. Rahman - Hasbullah, Yaaser; Abd. Rahman, Nurul Asra (2018)
Waste management is becoming a worldwide major issue . Glass which is non- biodegradable, is not suitable for addition to landfill; as such, recycling opportunities need to be investigated. Due to the high material consumption of the construction industry, the utilization of waste glass as a partial replacement for fine aggregate in structural concrete is particularly attractive. This experiment aims to determine the effect of glass as partial replacement of fine aggregate in concrete. 35 concrete samples were tested at 7, 14 and 28 days, for glass replacement proportions of 0%, 15% and 25% each for two sizes of glass, 2mm and 5mm. Compression strength was done to test their strength. The results proved that highest strength activity given by the waste glass is after 28 days. The compressive strength of specimens with 15% of 5mm waste glass content were 15.16 N/mm2, higher than the concrete control and other specimens. Using glass dust waste in concrete is an interesting possibility for the economy on waste disposal sites and conservation of natural resources.